2010
DOI: 10.1016/j.jtcvs.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in rats causes partial impairment in insulin response associated with reduced fatty acid oxidation and mitochondrial gene expression

Abstract: Objective: Myocardial infarction leads to contractile dysfunction. In patients with diabetes, impaired contractility has been associated with the loss of insulin effects and mitochondrial dysfunction. We assessed cardiac insulin sensitivity and mitochondrial and contractile function in rats after ligation of the left coronary artery. Methods: At 2 weeks after left coronary artery ligation, we performed echocardiography in vivo and assessed the substrate use and insulin response in the isolated working heart an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…In the presence of systolic dysfunction, cardiac glucose uptake was found to be decreased following aortic constriction in mice 57 but unchanged in rats with myocardial infarction, 58 and increased in Dahl salt-sensitive rats. 48 In compensated hypertrophy, induced by abdominal aortic constriction, glycolysis was modestly increased without changes in glucose oxidation.…”
Section: Cardiac Metabolism In Heart Failurementioning
confidence: 95%
“…In the presence of systolic dysfunction, cardiac glucose uptake was found to be decreased following aortic constriction in mice 57 but unchanged in rats with myocardial infarction, 58 and increased in Dahl salt-sensitive rats. 48 In compensated hypertrophy, induced by abdominal aortic constriction, glycolysis was modestly increased without changes in glucose oxidation.…”
Section: Cardiac Metabolism In Heart Failurementioning
confidence: 95%
“…Similarly, PGC-1 β was shown to be responsible for mitochondrial dysfunction resulting from accelerated myocardial hypertrophy following pressure overload [126]. Furthermore, expression of p38-MAPK was found to be reduced after MI, leading to an impaired capability to oxidize fatty acids, which in turn contributes to LV dilatation [127]. Interestingly, in vivo overexpression of TFAM in a mouse model of MI improved mt-DNA copy number and mitochondrial complex activity, while reducing myocyte hypertrophy, interstitial fibrosis, apoptosis, and chamber dilatation, thus slowing down the overall progression of LV remodeling [128].…”
Section: Mitochondrial Dysfunctionmentioning
confidence: 99%
“…In contrast, the data on cardiac glucose use are less consistent [4345]. In the presence of systolic dysfunction, cardiac glucose uptake was decreased in mice after aortic constriction [43], while unchanged in rats with myocardial infarction [46], and increased in Dahl salt-sensitive rats [39]. The impaired glucose oxidation that parallels systolic dysfunction might be attributable in part to mitochondrial dysfunction, reduced expression of genes involved in glycolysis and glucose oxidation, or decreased abundance of the PDH complex [39, 47].…”
Section: Mitochondrial Dysfunction In Diabetic Heartmentioning
confidence: 99%
“…The impaired glucose oxidation that parallels systolic dysfunction might be attributable in part to mitochondrial dysfunction, reduced expression of genes involved in glycolysis and glucose oxidation, or decreased abundance of the PDH complex [39, 47]. Osorio et al showed increased glucose oxidation rates in failing dog hearts induced by rapid pacing [46], and Dávila-Román et al demonstrated higher total rates of glucose use in patients with idiopathic dilated cardiomyopathy [48]. Thus the changes in glucose oxidation in cardiac myocytes may depend on both the stage and the pathogenesis of heart failure.…”
Section: Mitochondrial Dysfunction In Diabetic Heartmentioning
confidence: 99%